Volatility persistence and returns spillovers between oil and gold Prices: analysis before and after the global financial crisis (2016)
This paper investigated volatility persistence and returns spillovers between oil and gold markets using daily historical data from 1986 to 2015 partitioned into periods before the global crisis and after the crisis. The log-returns, absolute and squared log-returns series of these asset prices were used as proxy variables to investigate volatility persistence using the fractional persistence approach. The Constant Conditional Correlation (CCC) modelling framework was applied to investigate the spill over effects between the asset returns. The volatility in the gold market was found t be less than that at the oil market before and after the crisis periods. The returns spill over effect was bid irectional before the crisis period while it was unidirectional from gold to oil market after the crisis. The fact that there was no returns spill over running from oil to gold after the crisis suggested a measure of optimumal location weights and hedge ratio. The results obtained are of practical implications for port folio managers and decision managers in these two ways: gold market should be used as a hedge against oil price inflationary shocks; and the volatility at the oil market can be used to determine the behaviour of gold market.